The Health Impacts of Severe Climate Shocks in Colombia (2014)
This paper studies the link between severe weather shocks in Colombia and municipality-level incidence of dengue and malaria. The unexpectedly high variability of the 2010 rainfalls relative to previous periods and their regional heterogeneity are exploited as an identification strategy. A differences-indifferences (DD) strategy is thereby implemented where the period 2007-2009 is defined as the pre-treatment period and 2010-2011 as the post-treatment period. The treatment group is all municipalities that experienced higher intra-year rain variability in 2010 than in 2007-2009. The results from the different specifications confirm that the relationship between climate events and vector-borne diseases is intricate. The 2010 weather shocks are associated with not only an increase in the number of dengue cases, in the case of high variability (but not extreme) yearly rain, but also a decrease in its incidence, in particular in the presence of extreme rain events. Floods seem to have decreased the number of dengue cases.